Carboniferous sedimentary provenance and tectonic setting in the Darbut region of Western Junggar (NW China): evidence from mineralogy, geochemistry and detrital zircon U–Pb dating. Issue 5 (September 2021) - Weng, Kai; Dong, Yunpeng; Xu, Xueyi; Ma, Zhongping; Chen, Bo
No abstract available